Rhetoric and prosody of judicial discourse in mass media (Eurasian Journal of Philology Science and Education, 2022)
We inevitably deal with the spread of the legal practice to the masses to inform the population about current criminal cases and their court decisions. There are few works dedicated to the studies of the rhetoric and prosody of the judicial discourse both in domestic and international science space. This article is devoted to the study of the rhetorical function of prosody in judicial discourse. It is known that the interest in the study of the language prosody has begun to manifest with the advent of new computer programs that allow analyzing the prosody, especially, the temporal variables, such as speed, duration, intonation, and pause of speech. Accordingly, this article aims to work on the study of the rhetorical function of prosody in judicial discourse. Taking into account the complexity of the polyfunctionality of prosody as a subject of research, the study of the prosodic function of judicial discourse in mass media in the context of rhetoric allows understanding the meaning of prosodic processes in speech and determining the intention of news. The study was based on the news coverings of the criminal case of Ezra McCandles, which was considered in the United States from 2018 to 2020. The article used research methods such as rhetorical discourse analysis, as well as acoustic analysis using the Praat computer program. The prosodic analysis of judicial discourse in the context of rhetoric revealed the prosodic narrative techniques such as alternating intensity, rise, and fall of the tone, speech pauses, which aimed to impact the perception of the case by the listeners.